2023
DOI: 10.1073/pnas.2201076120
|View full text |Cite
|
Sign up to set email alerts
|

Divergent sensory and immune gene evolution in sea turtles with contrasting demographic and life histories

Abstract: Sea turtles represent an ancient lineage of marine vertebrates that evolved from terrestrial ancestors over 100 Mya. The genomic basis of the unique physiological and ecological traits enabling these species to thrive in diverse marine habitats remains largely unknown. Additionally, many populations have drastically declined due to anthropogenic activities over the past two centuries, and their recovery is a high global conservation priority. We generated and analyzed high-quality reference genomes for the lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 130 publications
1
8
0
Order By: Relevance
“…Bacterial or fungal infections have been suggested as a potential cause (Bell et al, 2003), but in a study of the Columbian nesting population, the authors found no impact of microorganisms on hatching success (Patino‐Martinez et al, 2012). Furthermore, Bentley et al (2023) recently found that leatherbacks exhibit extremely low genetic diversity and have a higher genetic load compared with other reptiles. The authors suggested these factors may contribute to the high levels of embryonic death exhibited in leatherback turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial or fungal infections have been suggested as a potential cause (Bell et al, 2003), but in a study of the Columbian nesting population, the authors found no impact of microorganisms on hatching success (Patino‐Martinez et al, 2012). Furthermore, Bentley et al (2023) recently found that leatherbacks exhibit extremely low genetic diversity and have a higher genetic load compared with other reptiles. The authors suggested these factors may contribute to the high levels of embryonic death exhibited in leatherback turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most important ecological characteristic that these three taxa have in common is their independent conquest of cold environments (Garcia-Porta et al 2019). Taking into consideration the increasing evolutionary importance attributed to microchromosomes (Uno et al 2012; Srikulnath et al 2021;Waters et al 2021), and the apparently direct involvement of some of their gene contents in differential adaptations of other sqamate reptiles (Bentley et al 2023), it can not be discarded that their loss has been due to selection, in a still unspeci ed way.…”
Section: Discussionmentioning
confidence: 99%
“…To identify potentially active copies of TEs, we analysed the long-read transcriptome (IsoSeq) data from 3 different tissues (brain, ovaries, and lungs) of D. coriacea available at the NCBI database under identi ers SRR9594996, SRR9594994, and SRR9594995, respectively (Bentley et al 2023). IsoSeq reads were mapped to the genome of D. coriacea (GCF_009764565.3) with minimap2 (Li 2018), applying the additional parameters -ax splice -uf -secondary = no -C5 -O6,24 -B4.…”
Section: Methodsmentioning
confidence: 99%